2019
DOI: 10.1108/bepam-10-2017-0090
|View full text |Cite
|
Sign up to set email alerts
|

Training gaps in the adoption of building information modelling by Nigerian construction professionals

Abstract: Purpose The opportunities that the building information modeling (BIM) mode of project delivery presents warrant the need for the construction professionals to be adequately trained on BIM technology and processes. The purpose of this paper is to assess the training gaps that exist between the perceived and expected knowledge of BIM practice among construction professionals in Nigeria. Design/methodology/approach The study was carried out through a structured questionnaire survey administered on identifying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
3
11
0
Order By: Relevance
“…Despite the disparity in the ranking of this barrier as shown in Table 5, no significant differences were found as evidenced by the results of the Kruskall-Wallis one-way analysis of variance (ANOVA) for "Data and intellectual property issues" (p 5 0.104 > 0.05). The findings are further consistent with previous studies which identified training gaps in adopting BIM with quantity surveyors amongst the construction professionals in most need (Oyewole and Dada, 2019).…”
Section: Kruskal Wallis (One-way Analysis Of Variance (Anova))supporting
confidence: 92%
See 1 more Smart Citation
“…Despite the disparity in the ranking of this barrier as shown in Table 5, no significant differences were found as evidenced by the results of the Kruskall-Wallis one-way analysis of variance (ANOVA) for "Data and intellectual property issues" (p 5 0.104 > 0.05). The findings are further consistent with previous studies which identified training gaps in adopting BIM with quantity surveyors amongst the construction professionals in most need (Oyewole and Dada, 2019).…”
Section: Kruskal Wallis (One-way Analysis Of Variance (Anova))supporting
confidence: 92%
“…Recently, there have been studies regarding BIM barriers in developing countries like Ghana (Oteng et al, 2018), Pakistan (Akdag and Masqood, 2019) and Yemen (Gamil and Rahman, 2019) but little research has been carried out in Nigeria context (Amuda-Yusuf et al, 2017;Anifowose et al, 2018;Hamma-adama and Kouider, 2019;Babatunde et al, 2020a). Whist there have been some studies on BIM within the Nigerian context, these have been limited to exploring the barriers to the incorporation of BIM into quantity surveying (QS) undergraduate curriculum in Nigerian universities, albeit from the lenses of students and academics ; identification of measures to improve the usage of BIM in the Nigerian building industry (Onungwa et al, 2017); assessment of the BIM training gaps (Oyewole and Dada, 2019); impact of BIM on collaboration (Onungwa and Uduma-Olugu, 2016); BIM awareness (Olapade and Ekemode, 2018); Barriers to BIM in SMEs (Saka and Chan, 2020); Benefits (Olawumi and Chan, 2019a), and drivers / barriers for BIM implementation Babatunde et al, 2020a). More so, the higher levels of BIM awareness in Nigeria do not necessarily translate into implementation (Saka and Chan, 2019c).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, for studies that examined BIM adoption, awareness and implementation among AEC firms (Olugboyega and Aina, 2016; Onungwa et al , 2017; Ganiyu et al , 2018; Olabode and Umeh, 2018). Few studies assessed BIM training gaps among construction professionals (Oyewole and Dada, 2019). Few other studies examined BIM maturity level among AEC firms, comprising architectural firms, facility management firms, quantity surveying firms and structural engineering firms (Babatunde et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, studies that examined BIM adoption, awareness, and implementation among Architecture, Engineering, and Construction (AEC) firms (see Olugboyega and Aina, 2016;Onungwa et al, 2017;Ganiyu et al, 2018;Olabode and Umeh, 2018). Few studies assessed BIM training gaps among construction professionals (see Oyewole and Dada, 2019). Few other studies examined BIM maturity level among AEC firms comprised architectural firms, facility management firms, quantity surveying firms, and structural engineering firms (see Babatunde et al, 2019).…”
Section: Introductionmentioning
confidence: 99%